2020
DOI: 10.1111/jmi.12972
|View full text |Cite
|
Sign up to set email alerts
|

Release of insulin granules by simultaneous, high‐speed correlative SICM‐FCM

Abstract: Summary Exocytosis of peptides and steroids stored in a dense core vesicular (DCV) form is the final step of every secretory pathway, indispensable for the function of nervous, endocrine and immune systems. The lack of live imaging techniques capable of direct, label‐free visualisation of DCV release makes many aspects of the exocytotic process inaccessible to investigation. We describe the application of correlative scanning ion conductance and fluorescence confocal microscopy (SICM‐FCM) to study the exocytos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We investigate the difference of instance intensity and volume on insulin vesicle and mitochondrion respectively. The results from our tool agree well with previous studies [ 39 42 ]. Moreover, with higher recognition accuracy, our tool reveals the significant variance of the volume and intensity of both insulin vesicle and mitochondria instances under different treatments, providing a more detailed description of the subcellular structures, which will is expected to facilitate future mechanistic studies of β -cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We investigate the difference of instance intensity and volume on insulin vesicle and mitochondrion respectively. The results from our tool agree well with previous studies [ 39 42 ]. Moreover, with higher recognition accuracy, our tool reveals the significant variance of the volume and intensity of both insulin vesicle and mitochondria instances under different treatments, providing a more detailed description of the subcellular structures, which will is expected to facilitate future mechanistic studies of β -cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our tool and connected regions labeling produce organelle instances which lie within the experimentally determined ranges, compared to Watershed and Watershed + Gaussian filer methods. The diameter of an insulin vesicle is approximately 200 nm [ 39 41 ], whose volume equals to 170 voxels in our tool results. The volume of mitochondrion ranges from 300 to 7500 voxels according to the baffle model [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the optical readout (see dedicated section below) provides a complementary imaging of the objects (or function). Bednarksa et al used correlative high-speed SICM and confocal microscopy to measure the kinetics of exocytosis of single granules of insulin from the top surface of single β . They synchronized the z -piezo actuator for nanopipette vertical positioning with another piezo used to vertically move the objective of a confocal microscope to achieve confocal autofocusing.…”
Section: High-throughput Scanning Ion Conductance Microscopymentioning
confidence: 99%
“…Bednarksa et al used correlative high-speed SICM and confocal microscopy to measure the kinetics of exocytosis of single granules of insulin from the top surface of single β. 125 They synchronized the z -piezo actuator for nanopipette vertical positioning with another piezo used to vertically move the objective of a confocal microscope to achieve confocal autofocusing. The system allowed topography measurements of areas as large as 4 μm × 4 μm with a scanning speed as fast as 18 s/frame, while simultaneously acquiring confocal microscopy images of insulin granules inside and on the surface of single cells.…”
Section: High-throughput Scanning Ion Conductance Microscopymentioning
confidence: 99%
“…They proposed a new insulin signal transduction mechanism which helps to understand the microvilli structure of insulin and renal tubular epithelial cells dynamic regulation 75 . Bednarska et al revealed the dynamic mechanism of the complete fusion of insulin vesicles through SICM‐FCM and provided new directions and ideas for studying the process of exocytosis 60 . SICM can also be used to explore the effects of different concentrations of paraformaldehyde on the mechanical properties of cells, thus it provides a new way to improve the scheme of cell fixation 76 …”
Section: Application Of Sicm In Biomedical Researchmentioning
confidence: 99%